The influence of childhood asthma on puberty and height in Swedish adolescents. Issue 5 (5th June 2015) - Protudjer, Jennifer Lisa Penner; Lundholm, Cecilia; Bergström, Anna; Kull, Inger; Almqvist, Catarina
Abstract Background Evidence relating to the effect of asthma on puberty or height is inconclusive. We aimed to examine whether the exposure of childhood asthma, including timing and phenotypes, and inhaled corticosteroid (ICS) use is either cross‐sectionally or longitudinally associated with the outcomes of pubertal staging or height. Methods This study employed data from a longitudinal, population‐based cohort of Swedish children (born 1994–1996). At ages 1, 2, 4, 8, and 12 years, parent‐reported data on asthma and ICS use in the previous 12 months were collected. At 8 and 12 years, height was ascertained at a clinical visit, and child‐reported, respectively. At 12 years, children answered puberty‐related questions. Results Retention through 12 years was 82% (3366/4089). Participants without puberty data (n = 620) were excluded, yielding a study population of 2746 (67%). Asthma at 8 years, including timing of onset and phenotypes, was not statistically significantly associated with pubertal staging in adjusted models. Children with asthma averaged 0.93 cm (95% CI 0.35–1.50) shorter than children without asthma. Children with asthma using ICS were 1.28 (95% CI 0.62–1.95) shorter than those with asthma without using ICS. Conclusions We found no consistent association between asthma and pubertal staging. Children with asthma were shorter than those without asthma. Moreover, children with asthma using ICS were shorter than those not using ICS.